Species richness and endemicity of the herpetofauna of South and Southeast Asia - Das, I.; van Dijk, Peter Paul (National University of Singapore, 2013)
Southern and Southeast Asia, extending from Pakistan to islands on the Sunda Shelf of the Indo-Malayan Archipelago and the Philippines, are home to a highly diverse herpetofauna. Based on the ecoregional classifi cation presented in Wikramanayake et al. (2002) and a species listing database from 2000, we analyse herpetofaunal distribution, while taking into account the uneven survey efforts in different ecoregions. Larger ecoregions that are adequately sampled show greater species richness, contain more diverse topography and support a mosaic of habitat subtypes. In contrast, some of the smaller ecoregions are restricted to a specifi c habitat type. A latitudinal gradient in species diversity is evident and the ecoregions of the highest species richness straddle the equator, presumably for their tropical rainforests, aseasonal climate, high precipitation, and complex vegetation. Rainforests of lowlands and low elevation regions are richest in species richness, due to structural complexity and climatic conditions. Examples of vicars are evident in insular-insular or continental-insular comparisons of assemblages, many being the presumed result of Pleistocene sea level lowering. Endemicity is high on islands, waif dispersal selectively biased towards certain large species of reptiles, although amphibians are excluded. Herpetofaunal communities in different rainforest ecoregions share relatively few species: the same genera are usually present, but represented by different species. In many cases, these species are restricted-range or locally endemic species. The herpetofauna of monsoon forests is relatively similar within mainland Southeast Asia, but the herpetofaunal species inhabiting two mountain sites in close proximity can be remarkably different. A majority of regionally endemic species inhabit rainforest ecoregions, and particularly montane areas. A number of regional endemics inhabit monsoon forest or specialised habitats (caves, open rivers or swamps), but tend to occur locally at spots across a wide geographic range. Knowledge of the taxonomy of the region’s herpetofauna remains poor, but suffi cient to indicate regions of high conservation value, as well as priority areas for survey. Reptiles and amphibians are also known to be of value as indicator species for habitat quality and to for learning the earth’s evolutionary and biogeographic processes.